Look closer, draw better : expert techniques for realistic drawing - Ewing, Kateri (Rockport, 2019)
Look Closer, Draw Better is a step-by-step technique book based on observational drawing by a noted American artist and author-written for advanced beginners and up, offering techniques in graphite, charcoal, ink, and watercolour wash. Are you looking to make a leap in the quality of your artwork? Are you looking for new perspectives on the art of drawing? Or maybe you want to bring more poetry and presence to your work. Look Closer, Draw Better will help you reach your goals with projects that explore graphite, charcoal, ink, and watercolour wash, emphasizing techniques that Kateri Ewing has refined over years of practice and teaching. Ewing teaches by training your eye to see subjects clearly in contour, line, and shadow, while you learn to make marks with tools that are expressive of what we really see. Her focus is on nature-birds, flowers, and plants that can be closely observed. Discover the techniques for capturing the delicacy of feathers, the natural blemishes on a piece of fruit, the veins and velvety texture of a leaf-all the tiny details that enhance the realistic quality of a drawing. Ewing takes you carefully through every step. Let Look Closer, Draw Better inspire and transform your artistic eye.